PERAN HYDRAULIC LIFT JA MBU METE PADA PEMELIHARAAN LENGAS TANAH DAN STATUS AIR JAGUNG SAAT KEKERINGAN / The Role of Cashew Hydraulic Lift in Maintaining Soil Moisture and Water Status of Maize under Drought Condition - Joko Pitono; Nur Maslahah; Setiawan Setiawan (Jurnal Penelitian Tanaman Industri, 2017)
Hydraulic lift (HL) plants are reported to share water to other plants during drought period. Our previous study found cashew had HL capability, however it was still unclear for sharing water. This study was carried out at the greenhouse of Cimanggu from May to November 2016, to evaluate whether the cashew HL could share water during drought period and its effect on maintaining soil moisture, leaf water potential, transpiration, and photosynthesis of maize. The cashew variety, B-02 and maize variety, Lamuru, planted side by side in the special designed pots, and setted in three conditions, i.e. full irrigation (B), drought without cashew HL access (K), and drought with cashew HL access (H). All of the treated plants were setted in a randomized block design with nine replicates. The results showed the cashew HL could share water to themaize. During the advanced drought periods, the soil moisture of maize was maintained higher ± 2.5% compared to it without access of cashew HL. It promoted water status of maize to be better at 8th day after drought treatment, with decrease of leaf water potential, transpiration, and photosynthesis respectively just about 30%, 36% and 32% of the values on the well irrigated condition. However, those decreased values reached 40%, 70% and 57% for the maize without cashew HL access. This study showed the cashew HL quite effectively induced the sharing water to the maize during drought periods, and alleviated the worse effects of drought stress, so that the maize could maintain a good soil moisture and tissue water status.Keywords: cashew, hydraulic lifts, sharing water, leaf water potential,maize AbstrakTanaman hydraulic lift (HL) dilaporkan dapat memasok air pada tanaman lain di sekitarnya saat periode kekeringan. Hasil studi sebelumnya menunjukkan jambu mete memiliki kemampuan HL, namun belum diketahui potensi pasokan airnya. Penelitian ini dilakukan di komplek rumah kaca Cimanggu antara Mei-November 2016 dengan tujuan mengevaluasi kemampuan pasokan air dari hydraulic lift jambu mete pada periode kekeringan dan efeknya terhadap status air jaringan jagung yang tumbuh di sekitarnya. Jambu mete varietas B-02 dan jagung varietas Lamuru ditanam berdampingan pada pot dengan desain khusus, yang diatur dalam tiga kondisi perlakuan, yakni selalu berkecukupan air (B), kekeringan tanpa ada akses HL jambu mete (K), dan kekeringan dengan akses HL jambu mete (H). Ketiga perlakuan kondisi tanaman tersebut ditempatkan di rumah kaca dalam rancangan acak kelompok dengan sembilan ulangan. Hasil penelitian menunjukkan HL jambu mete dapat memasok air pada jagung, sehingga pada periode kekeringan tingkat lanjut, lengas tanahnya menjadi lebih tinggi ± 2,5% dibandingkan jagung tanpa akses HL jambu mete. Adanya pasokan air tersebut menyebabkan status air jaringan jagung selama periode kekeringan menjadi lebih baik dengan tingkat penurunan nilai dari kondisi kecukupan air pada potensial air daun, transpirasi, dan fotosintesis berturut-turut hanya sekitar 30%, 36%, dan 32%, dibandingkan penurunan nilai tersebut pada kondisi tanpa akses HL jambu mete yang mencapai 40%, 70%, dan 66%. Hasil penelitian ini memperlihatkan pasokan air pada jagung oleh HL jambu mete cukup efektif pada periode kekeringan, dan membantu meringankan efek stres kekeringan pada jagung sehingga dapat memelihara status air jaringannya tetap baik.